2023
DOI: 10.3389/fsurg.2022.1064272
|View full text |Cite
|
Sign up to set email alerts
|

Association between epidural-related maternal fever and short-and long-term prognosis of parturients: A prospective observational study

Abstract: We aimed to explore the association between epidural-related maternal fever (ERMF) and prognosis of parturients. 159 parturients who underwent vaginal delivery under labor epidural analgesia (LEA) received noninvasive continuous core body temperature monitoring. 122 of them completed the 42-day postpartum follow-up. Parturients with body temperature ≥38°C during labor were categorized as the Fever group, while the others were categorized as the No-Fever group. Compared to No-Fever group, Fever group had a grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Laboring women often require the quicker onset provided by the dural puncture epidural technique and early-NA to alleviate pain during cervical dilation of less than 2-3 cm [ 13 , 14 ]. At the same time, NA is associated with a prolonged duration of first, second and total stage of labor [ 2 , 15 , 16 ], intrapartum CD, operative vaginal delivery [ 15 ], intrapartum fever [ 3 , 4 ], and adverse maternal and neonatal outcomes [ 17 ]. With the implementation of the three-child policy, there has been an increase in multiparous women opting for vaginal delivery in China.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laboring women often require the quicker onset provided by the dural puncture epidural technique and early-NA to alleviate pain during cervical dilation of less than 2-3 cm [ 13 , 14 ]. At the same time, NA is associated with a prolonged duration of first, second and total stage of labor [ 2 , 15 , 16 ], intrapartum CD, operative vaginal delivery [ 15 ], intrapartum fever [ 3 , 4 ], and adverse maternal and neonatal outcomes [ 17 ]. With the implementation of the three-child policy, there has been an increase in multiparous women opting for vaginal delivery in China.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have consistently reported a significant increase in the incidence of intrapartum fever among parturients who received NA [ 3 , 4 , 19 ]. Intrapartum fever was associated with intrapartum CD, operative vaginal delivery, and PHH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, antibiotic administration is recommended to manage maternal fevers (Goetzl, 2023). Although approximately 90% of pregnant women with ERMF show improvement within hours of delivery (Gonen et al, 2000), studies on the relationship between ERMF and long-term outcomes are limited (Li et al, 2022). While the current management of ERMF presents challenges, the potential role of IL-1ra in preventing ERMF represents an exciting frontier in maternal healthcare and will be the focus of the following discussion.…”
Section: Challenges In Managing Ermfmentioning
confidence: 99%